Memória e identidade em Carlos Heitor Cony: uma nálise de Quase memória. Quase romance - Przybylski, Mauren Pavão (Anuário de Literatura, 2003)
The present text intends to analyze Quase-Memória. Quase Romance from anidentitarian and memorialistic stand point. Recognizing Carlos Heitor Cony Father, CarlosHeitor Cony Son and the Package as relevant charecters, which have a sometimes repulsi-ve inter-relation, we will try, through this concoction of fiction and reality, to analyze thenarrative.